Chemical climatology of the southeastern United States, 1999–2013 - G. M. Hidy (Atmospheric Chemistry and Physics, 2014)
A series of experiments (the Southern Oxidant and Aerosol Study – SOAS) took place in central Alabama in June–July, 2013 as part of the broader Southern Atmosphere Study (SAS). These projects were aimed at studying oxidant photochemistry and formation and impacts of aerosols at a detailed process level in a location where high biogenic organic vapor emissions interact with anthropogenic emissions, and the atmospheric chemistry occurs in a subtropical climate in North America. The majority of the ground-based experiments were located at the Southeastern Aerosol Research and Characterization (SEARCH) Centreville (CTR) site near Brent, Alabama, where extensive, unique aerometric measurements of trace gases and particles and meteorology were made beginning in the early 1990s through 2013. The SEARCH network data permits a characterization of the temporal and spatial context of the SOAS findings. Our earlier analyses of emissions and air quality trends are extended through 2013 to provide a perspective for continued decline in ambient concentrations, and the implications of these changes to regional sulfur oxide, nitrogen–ozone, and carbon chemistry. The narrative supports the SAS program in terms of long-term average chemistry (chemical climatology) and short-term comparisons of early summer average spatial variability across the southeastern US at high temporal (hourly) resolution. The long-term measurements show that the SOAS experiments took place during the second wettest and coolest year in the 2000–2013 period, with lower than average solar radiation. The pollution levels at CTR and other SEARCH sites were the lowest since full measurements began in 1999. Changes in anthropogenic gas and particle emissions between 1999 and 2013 account for the decline in pollutant concentrations at the monitoring sites in the region. The data provide an opportunity to contrast SOAS results with temporally and spatially variable conditions in support of the development of tests for the robustness of SOAS findings.